2011
DOI: 10.1371/journal.pone.0023169
|View full text |Cite
|
Sign up to set email alerts
|

All Clinically-Relevant Blood Components Transmit Prion Disease following a Single Blood Transfusion: A Sheep Model of vCJD

Abstract: Variant CJD (vCJD) is an incurable, infectious human disease, likely arising from the consumption of BSE-contaminated meat products. Whilst the epidemic appears to be waning, there is much concern that vCJD infection may be perpetuated in humans by the transfusion of contaminated blood products. Since 2004, several cases of transfusion-associated vCJD transmission have been reported and linked to blood collected from pre-clinically affected donors. Using an animal model in which the disease manifested resemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
110
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 50 publications
3
110
0
3
Order By: Relevance
“…Multiple studies showed that TSE infectivity is present in the blood of experimental rodents, sheep with natural and experimental scrapie and experimental BSE, and deer affected with chronic wasting disease (CWD) (15)(16)(17)(18)(19)(20). PrP TSE has been successfully detected in the following: in whole blood of experimentally infected mice and hamsters, in sheep with natural scrapie and experimental BSE, and in white-tailed deer afflicted with CWD (21)(22)(23); in buffy coats of hamsters and sheep experimentally infected with scrapie (24 -26), as well as in plasma of mice and hamsters with scrapie; and in sheep and white-tailed deer naturally and experimentally infected with scrapie and CWD, respectively (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Multiple studies showed that TSE infectivity is present in the blood of experimental rodents, sheep with natural and experimental scrapie and experimental BSE, and deer affected with chronic wasting disease (CWD) (15)(16)(17)(18)(19)(20). PrP TSE has been successfully detected in the following: in whole blood of experimentally infected mice and hamsters, in sheep with natural scrapie and experimental BSE, and in white-tailed deer afflicted with CWD (21)(22)(23); in buffy coats of hamsters and sheep experimentally infected with scrapie (24 -26), as well as in plasma of mice and hamsters with scrapie; and in sheep and white-tailed deer naturally and experimentally infected with scrapie and CWD, respectively (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…In this context, the PrP transgenic Drosophila model we describe here could be considered to be of comparable, if not greater, sensitivity than transfusion studies in the natural host since plasma from scrapie-affected sheep is reported to contain less prion infectivity than whole blood [19]. In addition, the length of time required to bioassay plasma in PrP transgenic Drosophila was considerably less than that required by transfusion studies in the natural host [23].…”
Section: Discussionmentioning
confidence: 96%
“…Studies in ruminants have analysed bioassays of autologous whole or fractionated blood by the intravenous route [19,20]. These experimental transfusion studies have confirmed that all blood fractions prepared by protocols similar to those used in transfusion medicine can transmit prion disease [23,24]. In addition, prion transmission by transfusion of cellular blood fractions was not solely dependent on their infectious titre since prion disease was more efficiently transmitted with viable rather than non-viable leukocytes [20].…”
Section: Introductionmentioning
confidence: 93%
“…El hecho de que la PrP C se exprese en células sanguíneas del tipo monocito macrófago, podría representar un importante blanco para bloquear la replicación y la transmisión de la PrP Sc . Se han reportado evidencias de la posible transmisión de PrP Sc por sangre (23)(24)(25) , por lo tanto el silenciamiento de PrP C en el flujo sanguíneo podría reducir el nivel de infección o su rapidez de diseminación hacia el SNC.…”
Section: Discussionunclassified
“…The fact that PrP C is expressed in blood monocytes and macrophages, these cells could represent an important target for blocking PrP Sc replication and transmission. Evidences of possible PrP Sc transmission via blood have been reported (23)(24)(25) ; therefore, PrP C silencing in blood flow could decrease the level of infection or its speed to spread towards the CNS.…”
Section: Discussionmentioning
confidence: 99%